2007
DOI: 10.1038/sj.gt.3303042
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated carboxyl-terminal modulator protein gene transfection via aerosol in lungs of K-ras null mice

Abstract: The low efficiency of conventional therapies in achieving long-term survival of lung cancer patients calls for development of novel options. Aerosol gene delivery may provide the alternative for safe and effective treatment for lung cancer. Therefore, current study was performed to elucidate the potential effects of C-terminal modulator protein (CTMP) via aerosol on lung tumorigenesis. Lentiviral vector-CTMP was delivered into K-ras null lung cancer mice through the noseonly inhalation system for 30 min. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…However, the disruption of P. gingivalis-induced Akt phosphorylation is not caused by the diminished phosphorylation of the global network of IRS proteins, because activation of JNK and p70S6K are not affected in DIO BMM⌽ after P. gingivalis infection. Therefore, we explored the ability of DIO and FFAs to induce molecules such as CTMP, PP2A, and PTEN (28)(29)(30)(31). We found that CTMP is elevated in BMM⌽ from mice with DIO, and directly inhibits Akt phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the disruption of P. gingivalis-induced Akt phosphorylation is not caused by the diminished phosphorylation of the global network of IRS proteins, because activation of JNK and p70S6K are not affected in DIO BMM⌽ after P. gingivalis infection. Therefore, we explored the ability of DIO and FFAs to induce molecules such as CTMP, PP2A, and PTEN (28)(29)(30)(31). We found that CTMP is elevated in BMM⌽ from mice with DIO, and directly inhibits Akt phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang and colleagues suggested an antitumor activity of lentivirus-mediated CTMP gene therapy by using a K-ras null lung cancer mouse model (35). Simone and colleagues indicated the pro-apoptotic function of the Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…(9,10) Antibodies against phospho-Akt1 (Thr308), p21, p27, CDK4, cyclinD1, PCNA, BclxL, BCL2, uPA, uPAR, PAI-1, p53, p70S6K, phospho-p70S6K (Thr 389), and actin were obtained from Santa Cruz Biotechnology (Santa Cruz, CA, USA). Phospho-p53 (Ser20), phosphomTOR (Ser 2448), eIF4E and 4E-BP1, and mTOR antibodies were obtained from Cell Signaling (Beverly, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For aerosol delivery, the A=J mice were exposed to an aerosol of containing lentivirus-shRNA Pdcd4 solution (50 mL) containing 40 ng=mL of lentivirus-shRNA Pdcd4 for 1 month. (10) The A=J mice were allowed to inhale the aerosolized lentivirusshRNA Pdcd4 from the nebulizer for 30 min twice a week for 1 month, after which the mice were sacrificed, and lung samples were collected for further analysis. The untreated mice and mice treated with scramble shRNA (scrambled) were used as controls.…”
Section: Aerosol Delivery Of Lentivirus-shrna Pdcd4mentioning
confidence: 99%